The role of satisfaction with the performance appraisal: A comparative study between the public and private sectors - Rodrigues, R.; Gomes, C.; Junça Silva, A. (RBGN - Revista Brasileira de Gestão de Negócios, 2023)
Purpose – To study in Portugal (a) whether satisfaction with the performance appraisal (PA) differs depending on the sector where the workers perform their functions (private versus public), and (b) whether the relationship between workers’ perception of usefulness and accuracy of the performance appraisal process (PAP) and satisfaction with the outcome of their last PA is mediated by their satisfaction with the PAP.Theoretical framework – The PA has come to occupy a prominent place in organizations, because only it can be used to measure the skills of their workers and the way they contribute to achieving organizational success both qualitatively and quantitatively.Design/methodology/approach – Eight hundred and sixty-six professionals from the public and private sectors participated in this study. Data were collected using two multi-item questionnaires and two single-item scales.Findings – The results revealed that private sector employees showed higher levels of satisfaction with their PAs than those from the public sector. Furthermore, the results indicated that the usefulness and accuracy of the PAP had a significant and positive relationship with employees’ satisfaction with their last PA, and this relationship was partially mediated by satisfaction with the PAP, both in the public and private sectors.Practical & social implications of research – Regardless of the activity sector, it is fundamental that the PAP is useful and accurate; otherwise it is discredited, which prevents it from fulfilling its purpose and contributes to increasing the levels of worker dissatisfaction.Originality/value – This study clarified the differences that may emerge regarding satisfaction with PAs between the Portuguese public and private sectors. In addition, this is the first national or international study to analyse the aforementioned constructs in an integrated manner